CLASSROOM ACTION RESEARCH AS PROFESSIONAL DEVELOPMENT OF TEACHERS IN INDONESIA - M. Noor Sulaiman Syah (Tarbawi : Jurnal Pendidikan Islam, 2016)
ABSTRACTThe approach historically used for professional development for classroom educators, where the emphasis is on 'training' and not on 'learning' is, quite simply, outdated. Classroom action research ?? with its cyclical nature of systematic investigation of teaching and learning, followed by data-driven improvements resulting from the outcomes of the investigations ?? provides not only a viable, but also valuable, professional development alternative. Following the development of improvement goals, the process of action research can be used to customize a teacher's professional development, allowing for a much more meaningful approach to professional growth. This approach permits teachers to investigate their own practice and to discover what will and will not work for their students in their classrooms. The integration of classroom action research with professional collaboration and with teacher evaluation is both discussed.  Keywords: Classroom Action Research, Professional Development